Recompositions territoriales et gouvernance des régions de montagne - Gilles Rudaz (Revue de Géographie Alpine)
The claim of a mountain specificity is at the heart of a number of contemporary collective actions. This process of territorial distinction redefines the status of mountains, reformulates the content of territorial projects, and redefines the actors and the relations they foster. This set of recompositions has implications on the governance of territories. The article, which discusses the actors’ positions and the legitimization of mountain entities, does not examine a particular case study but refers to a variety of examples taken in various areas of mountain of the world to illustrate the processes in progress.